Improving junior secondary school student's attitude towards mathematics through brainstorming learning strategy: a study in school effectiveness (2000)
Academic achievement stands out as one of the measures of school effectiveness; however, the poor achievement of students in school subjects like mathematics both at school and at public examinations has been a concern to mathematics educators. The failure rate may be due to students' attitude to subject which is likely to have its roots from how the subject is taught. This study, therefore, examines the effect of brainstorming on students' attitude in junior secondary school mathematics. The study adopted a quasi experimental design with pre test- post test control group. Two instruments: response (Student Questionnaire) and stimulus (experimental package) were used to collect data. The result shows that students exposed to brainstorming strategy developed positive attitude to mathematics than those in the control group. It is, therefore, recommended that teachers should be taught to use brainstorming strategy in the teaching of mathematics in school.